Effectiveness of the performance of the blood management agency (bpbd) in treatment of post earthquake natural disaster in lombok province nusa tenggara barat. - Al Riza, Faisal; R, Emy Kholifah (Universitas Muhammadiyah Jember, 2019)
This study uses a performance evaluation used by the West Nusa Tenggara Provincial Disaster Management Agency to measure organizational performance after an earthquake. The research method used in this study is that qualitative research carried out in the research conducted is descriptive research that discusses the analysis of events. The unit of analysis in this study is the effectiveness of the performance evaluation of the Regional Disaster Management Agency of West Nusa Tenggara Province. The type of research used by the authors in this study is qualitative descriptive. Data collection techniques are interviews, observations and documents related to research. The data analysis technique in this study was carried out qualitatively. Objectives / goals / plans in achieving the goals, objectives, mission, organizational vision contained in the formulation of strategic planning (strategic planning) of an organization. Then, the results of the assessment that shows the results of systematic analysis and evaluation results based on performance indicators, which involve indicators of input, output, results, benefits, and changes. Performance measurement is used as a basis for achieving success and completion of implementation in accordance with the goals and objectives set in the framework of realizing the vision and mission. Stages of measuring organizational performance according to tactics starts from clarity of purpose, clarity of strategy, process of analysis and policy formulation, planning, planning programs, availability of facilities and infrastructure and a system of supervision and control. The results of this study explain the measurement system applied by the Regional Disaster Management Agency of West Nusa Tenggara Province has not been effective. Because the performance assessment carried out by the Regional Disaster Management Agency of the Province of West Nusa Tenggara is not systematically arranged and can only be accessed in the Government Agency Performance Accountability Report.